The Truth Behind the Label: Ensuring Fairness and Legal Liabilities in Skincare Ingredient Overclaims - Felicia Margaret; Dripsy Teresa P. Sapni; Evi Kongres (Mimbar Keadilan, 2025)
Recently, interest in skincare products has grown dramatically. As a result, there is intense competition due to the emergence of numerous new skincare brands. Some skincare brands, in their pursuit of greater profits, resort to unethical practices, such as overclaiming the ingredients on the packaging. These exaggerated claims not only deceive consumers but also result in a significant discrepancy between the promised and actual ingredient composition which lead to potential harm to consumers' health and financial losses. This research's legal concern is corporate actors' liability for making exaggerated claims about the ingredients’ composition that harms consumers’ rights. This research offers a novel perspective to the legal protection for consumers by focusing specifically on ingredients overclaims in skincare products that do not match reality. The analysis is based on articles on consumer rights in Law No. 8/1999 using the normative legal method. Through this research, it was found that the legal responsibility of business actors is often hindered by gaps in law enforcement processes. These challenges, such as inadequate regulation enforcement and lack of transparency, must be addressed to mitigate the widespread phenomenon of ingredient overclaims in the skincare industry. In conclusion, effective legal safeguards and more stringent monitoring mechanisms are essential to uphold consumer rights and ensure fair business practices within the skincare sector.